PENINGKATAN KAPASITAS KADER PALANG MERAH REMAJA (PMR) SEBAGAI KONSELOR SEBAYA PADA AGEN PEDULI KESEHATAN MENTAL SEBAYA - Sosialita, Tiara Diah; Nisa, Valina Khiarin; Surjaningrum, Endang Retno (Jurnal Abdi Insani, 2024)
This community service activity was carried out based on the results of a needs analysis of the incidence of psychological problems at SMK 4 Pancasila Ambulu, Jember Regency. Guidance and Counseling (BK) revealed a total of 84 cases found during the first trimester in 2023, including conflicts with families, bullying among teenagers, academic stress, and interpersonal conflicts that led to psychological problems in students. This is faced with limited resources so that the range of handling of students' psychological problems is ineffective. Therefore, this community service aims to form agents of change who care about mental health to help deal with adolescent psychological problems through increasing the capacity of PMR cadres as peer counselors. The activities were carried out in several forms, including Instagram Live for a total of 2 (two) sessions with the topics of Variety of Adolescent Mental Disorders and Detection of Adolescent Mental Disorders, peer counselor training, as well as discussion forums and peer counselor role-play to equip cadres with the knowledge and skills to carry out their role as counselors. The results showed that the capacity of the cadres had significantly increased in knowledge and skills as peer counselors (ES = 1.54). Along with increased capacity as peer counselors, cadres are able to effectively carry out their role as agents of peer mental health care. The cadres have handled the psychological problems of students at SMK 4 Pancasila Ambulu under the supervision of a psychologist. The empowerment of PMR cadres as peer mental health agents also received support and commitment from the school by formally establishing peer mental health care agents. The activities carried out by peer mental health care agents are expected to continue consistently so as to fully support student well-being.